Prevalence and risk factors associated with infection by Fasciola hepatica infection in cattle from peasant communities of Huancabamba (Piura-Peru) - Livia-Córdova, Giovana Nancy (2021)
This study aimed to determine the prevalence and risk factors associated with bovine fasciolosis in peasant communities of the Huancabamba province (Piura, Peru). In total, 360 samples of bovine faeces were collected in the districts of Huancabamba, Sondor, Sondorillo and Carmen de la Frontera. The stool samples were analysed using the Dennis sedimentation technique. Association of the presence of Fasciola hepatica eggs in the stool with the, sex and district of origin of the animals was evaluated. The results showed that 42.5% (95% CI: 37.3-47.8%) of animals were infected with F. hepatica. The highest probability of contracting fasciolosis in cattle was in the age group of 13-18 months (PR: 2.56; 95% CI: 1.51-4.28) and from the Sondorillo district (PR: 1.41; 95% CI: 1.04-1.94); Furthermore, being male was considered a protection factor (PR: 0.69; 95% CI: 0.53-0.90). The study showed a high prevalence of bovine fasciolosis in peasant communities of Huancabamba and its association with sex, age and place of origin.